Quantitative Approach to the Early Evaluation of Agricultural Reservoir Overflow Risk - Kyuhyun Shim; Youngkyu Jin; Dongwoo Ko; Joon Heo (Hydrology)
Climate change has intensified extreme rainfall events, increasing the risk of overflow in agricultural reservoirs originally designed without flood control. This study presents a practical approach for assessing the overflow risk by incorporating both hydrological and structural factors. The key evaluation indicators used for analysis were freeboard (height from the flood level to the embankment level), height from the full water level to the embankment level, inflow–outflow relationship, and flood management capacity relative to the watershed area. Based on the design standards, reservoirs in Jeollanam-do were selected for assessment, and those with a high overflow risk were identified. Rainfall runoff simulations were conducted to evaluate the reservoirs, and the results indicated that considering all four indicators allowed an effective assessment of overflow risk. Multiple regression analysis yielded an R2 value of 0.79, suggesting that the relationships among the selected indicators were suitable and had high explanatory power. The findings of this study are expected to provide a practical method for rapidly assessing reservoir overflow risks and developing effective flood response strategies.